Factor completely the given polynomial x(x + 20) + 11(x + 20) x(x + 20) + 11(x + 20)=

Question

Factor completely the given polynomial
x(x + 20) + 11(x + 20)

x(x + 20) + 11(x + 20)=

in progress 0
Dulcie 6 months 2021-08-17T11:44:49+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-17T11:45:58+00:00

    Answer:

    (x + 20)(x + 11)

    Step-by-step explanation:

    x(x + 20) + 11(x + 20) =

    Factor out the common factor of x + 20.

    = (x + 20)(x + 11)

    The binomials make it look complicated, but this is simpler than you think.

    Look at this simpler, but similar, example.

    Factor xy + 4y

    xy + 4y =

    You see clearly that y is a common factor, so you factor out y, and you get

    = y(x + 4)

    In your problem, you have

    x(x + 20) + 11(x + 20) =

    where (x + 20) is the common factor.

    You factor out the common factor, (x + 20). What is left? x + 11 as a factor, so you get

    (x + 20)(x + 11)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )